Activation of human heat shock genes is accompanied by oligomerization, modification, and rapid translocation of heat shock transcription factor HSF1. - Baler, R (1993)
Transcriptional activity of heat shock (hsp) genes is controlled by a heat-activated, group-specific transcription factor(s) recognizing arrays of inverted repeats of the element NGAAN. To date genes for two human factors, HSF1 and HSF2, have been isolated. To define their properties as well as the changes they undergo during heat stress activation, we prepared polyclonal antibodies to these factors. Using these tools, we have shown that human HeLa cells constitutively synthesize HSF1, but we were unable to detect HSF2. In unstressed cells HSF1 is present mainly in complexes with an apparent molecular mass of about 200 kDa, unable to bind to DNA. Heat treatment induces a shift in the apparent molecular mass of HSF1 to about 700 kDa, concomitant with the acquisition of DNA-binding ability. Cross-linking experiments suggest that this change in complex size may reflect the trimerization of monomeric HSF1. Human HSF1 expressed in Xenopus oocytes does not bind DNA, but derepression of DNA-binding activity, as well as oligomerization of HSF1, occurs during heat treatment at the same temperature at which hsp gene expression is induced in this organism, suggesting that a conserved Xenopus protein(s) plays a role in this regulation. Inactive HSF1 resides in the cytoplasm of human cells; on activation it rapidly translocates to a soluble nuclear fraction, and shortly thereafter it becomes associated with the nuclear pellet. On heat shock, activatable HSF1, which might already have been posttranslationally modified in the unstressed cell, undergoes further modification. These different process provide multiple points of regulation of hsp gene expression.